2014
DOI: 10.1007/s10439-014-1228-9
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Fetal Membranes with a Self-adhesive Ultrathin Polymeric Film: Evaluation in Mid-gestational Rabbit Model

Abstract: Preterm premature rupture of membranes (PPROM) causes 40% of all preterm births, affecting 150,000 women each year in the United States. Prenatal diagnostic procedures and surgical interventions increase incidence of adverse events, leading to iatrogenic membrane rupture after a fetoscopic procedure in 45% of cases. We propose an ultrathin, self-adherent, poly-L-lactic acid patch ("nanofilm") as a reparative wound closure after endoscopic/fetoscopic procedures. These nanofilms are compatible with application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The application of nanofilms during surgical and medical procedures may be facilitated by using thick supporting layers coupled with the membranes. Supporting sacrificial layers would allow manipulation and positioning of the nanofilm in the desired site, before dissolving in physiological media [23,24,39]. Finally, for some applications, nanofilms have been designed to be built directly onto the target device or tissue [36,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of nanofilms during surgical and medical procedures may be facilitated by using thick supporting layers coupled with the membranes. Supporting sacrificial layers would allow manipulation and positioning of the nanofilm in the desired site, before dissolving in physiological media [23,24,39]. Finally, for some applications, nanofilms have been designed to be built directly onto the target device or tissue [36,40].…”
Section: Discussionmentioning
confidence: 99%
“…3A. Previous studies have demonstrated that the thickness of ultra-thin polymeric films can be varied by simply regulating the spinning speed [22][23][24][25][26]. Fig.…”
Section: A Nanofilm Fabrication Imaging and Thickness Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 In the present work, arrays of freestanding polyvinyl alcohol (PVA) nanoneedles (or PVA replicas) were prepared using the water/alcohol-based PVA mold release agent Partall® Film #10 (Rexco). In particular, each fused silica mold containing an array of surface pores was coated with a thin layer of Partall® Film #10 using a foam paintbrush.…”
Section: Methodsmentioning
confidence: 99%
“…Research has revolved around preventing such complications as amniotic fluid leakage, preterm premature rupture of membranes and preterm labor. [4][5][6][7][8] Iatrogenic preterm premature rupture of the membranes (PPROM) is a significant factor contributing to perinatal outcome. Even a small diameter puncture, due to disruption of the fetal membranes increases the risk fo PPROM.…”
Section: Introductionmentioning
confidence: 99%